Urus sisa : an intelligent system for integrated solid waste management. - Abdul Manaf, Latifah; Basri, Hassan; Ahmad Basri, Noor Ezlin (Canadian Center of Science and Education, 2008)
UrusSisa is an expert system for selecting and designing solid waste technology. It can improve the process of selecting the best solid waste technology, and to make the knowledge of preliminary design of solid waste technology available. Knowledge based of UrusSisa consists of priority ranking using Analytical Hierarchy Process (AHP), and preliminary design of recommendation technology. AHP involves structuring multiple choice criteria into a hierarchy, assessing the relative importance of these criteria, and determining an overall ranking of the alternatives. Preliminary design of solid waste technology includes recycling, composting, incineration, and sanitary landfill. The performance of prototype has been tested by using case study.